2016
DOI: 10.1111/iju.13156
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted prompted voiding for management of urinary incontinence of nursing home residents: Efficacy and feasibility

Abstract: The management of urinary incontinence for nursing homes residents through ultrasound-assisted prompted voiding seems to reduce the absorbent cost and to partially improve care workers' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…The VAS score assessing the burden of voiding care was almost unchanged in the USAPV group, but it worsened in the CPV group. We previously reported significant improvement in two subscales of emotional and mental health of SF‐36 in care workers practicing USAPV . These results consistently indicate that USAPV did not deteriorate the care workers’ QOL.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The VAS score assessing the burden of voiding care was almost unchanged in the USAPV group, but it worsened in the CPV group. We previously reported significant improvement in two subscales of emotional and mental health of SF‐36 in care workers practicing USAPV . These results consistently indicate that USAPV did not deteriorate the care workers’ QOL.…”
Section: Discussionsupporting
confidence: 73%
“…The present study demonstrated that USAPV care significantly reduced daytime urine loss of incontinent nursing home residents compared with CPV care. We have previously shown that USAPV care decreases absorbent consumption in incontinent hospitalized adults and incontinent elderly living in nursing homes . This study is the first randomized controlled trial to confirm the significantly higher efficacy of USAPV than of CPV in managing UI, which is common in the elderly population.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This has important implications for patient care. As mentioned previously, prompted voiding with monitoring of intravesical urine volume using US bladder scanners is useful not only for improving urinary incontinence in elderly people, but also for reducing the cost of absorbents and improving care workers' quality of life . The Lilium α‐200 may provide a further advantage because it enables periodic automated monitoring of bladder volume, which could reduce the workload of care workers in determining the appropriate timing of prompted voiding.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ultrasound (US) devices are widely used to assess bladder volume, with several portable US bladder scanners being used in clinical practice with adequate accuracy and reproducibility . Previous reports have also suggested that prompted voiding with monitoring of intravesical urine volume using US devices is useful not only for improving urinary incontinence in elderly people, but also for reducing the cost of absorbents and improving care workers' quality of life . However, bladder urine volume in these studies could only be measured at regular intervals by a care worker or nurse rather than continuously.…”
Section: Introductionmentioning
confidence: 99%